Implicature Of Speech Acts in The Tradition of Rotenese Community Engagement in Tuatuka Eastern Part of Kupang, East Nusa Tenggara Province - Robot, Marselus; Djahimo, Santri E. P.; Budiman Jama, Karolus; Margareta, Karus Maria (Universitas Negeri Semarang, 2023)
Customary speech acts are usually presented metaphorically, and allegorically in order to imply certain meanings. Such language phenomena imply certain meanings that are textually biased. In linguistic studies, such a phenomenon is called implicature. What is unique in traditional speech acts (wedding proposal) is the implicature, both in the rules of language use and in the way the speech is delivered. Therefore, the conversation is structured in such a way as not to violate the maxims or principles of cooperation, politeness, and relevance in order to cooperate and reach an agreement. Pragmatics study is the theoretical framework used by the researchers for the discourse of betrothal speech acts in the tradition of the Rotenese Community in Tuatuka (Kupang). One of the important studies in pragmatics study is conversational implicature. Conversational implicature is a process of interpreting meaning based on both situation and context. The design of this research has been qualitative. The choice of this method is a consequence of the data collected in the form of words, sentences, symbols that will then be interpreted. Informants have been selected purposively, namely based on the research objectives to obtain accurate data. The data has been collected through in-depth interviews, recording, observation, and documentation studies. The research instruments have been a list of questions and an observation guide. Data validation has been conducted through Focus Group Discussion (FGD) and source triangulation. The data has then been analyzed through the steps of categorizing units, connecting research units with themes, and interpreting the relationship between thematic units. The research findings have shown that the implicature of engagement in the tradition of the Rotenese community in Tuatuka (Kupang) aims to build cooperation and establish good manners in order to obtain an agreement in the discussion about dowry. Two types of implicatures that are most productively used in the traditional marriage ceremony in the Rotenese ethnic tradition in Tuatuka are the maxim of quantity and relevance. Both maxims are very important in speech acts because (1) the cooperation to reach an agreement should be maintained, and (2) the misunderstandings between the two parties should be avoided, and (3) the harmonious relationships between the two families (the families of both female and male) should be fostered.